My Watch: Early Life and Military Volume I - Obasanjo, Olusegun (Kachifo Limited, 2014)
My Watch spans large expanses of time, from the pre-colonial Owu history, to early Abeokuta and the last throes of an independent city state at turn-of-the-century colonial Nigeria, to the early life of its author, his civil war experience, his stewardship of the transitional government of 1976-1979, the interregnum, his second appearance on the national scene as a civilian president on Nigeria's return to democracy in 1999, the completion of the first civilian-civilian transfer of government in Nigeria's history that inaugurated the Yar'Adua presidency and signalled the end of Obasanjo's tenure in office, and the year hence. Presented in three volume, this exquisitely narrated memoir, in turns intensely completes a trilogy of autobiographies - My Command, Not My Will, and My Watch - told by this sojourner of Nigerian and world history.
Keywords: Biography & Autobiographies; Memoir; Non-Fiction